Analisis Penggunaan Brizzi Sebagai Alat Transaksi Untuk Pembelian Tiket Masuk - Rahayu Permata Sari; Rina Anggraini (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
This study aims to find out how the implementation and the problems encountered in using Brizzi as a transaction tool for purchasing entrance tickets at the Kinantan Wildlife and Culture Park in Bukittinggi. This research is a field research with a qualitative approach. This research is descriptive and emphasizes the analysis side. The method of data collection is by observation and interviews. The research sample was taken using the convenience sampling method with the acquisition of 200 respondents. The data that has been obtained will then be analyzed using a deductive analysis method. The results of the study found that not 100% of respondents agreed to a change in access policy at the Kinantan Bukittinggi Wildlife and Cultural Park, an average of 21% of respondents could not accept this change (not adaptive) this was because when respondents visited the Wildlife and Cultural Park Kinantan Bukittinggi coincided with network disruptions and the slow performance of serving officers. With this policy change, there has been a decrease in visitors to the Kinantan Bukittinggi Wildlife and Cultural Park, before the use of Brizzi in 2018 the number of visitors was 818,379 visitors, and after using the Brizzi card in 2019 the number of visitors decreased by 88,674 visitors so that the total visitors in 2019 was 729,705 visitors. Efforts are needed so that problems do not happen again on all sides, both from the network system and services, so that a deeper evaluation is needed by the relevant parties, both from financial institutions that have the system, the Kinantan Bukittinggi Animal and Cultural Park as managers and the government as policy makers.